2017
DOI: 10.1016/j.maturitas.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D and sex hormones levels in men and women: The Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Introduction 25-hydroxyvitamin D [25(OH)D] deficiency has been associated with low testosterone levels in men, but there are conflicting reports of its associations with sex hormones in women. Less is known about whether these associations are independent of adiposity and lifestyle factors, and whether they differ by race/ethnicity. Aim To examine associations of 25(OH)D concentrations with sex hormone levels. Methods Cross-sectional analysis of 3017 men and 2929 women in a multi-ethnic cohort. Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 40 publications
5
53
2
Order By: Relevance
“…With regard to the bioavailability of testosterone, the largest study to date demonstrated a negative relationship between vitamin D and fT among postmenopausal women, 14 which is consistent with our findings. With regard to SHBG, the positive relationship with vitamin D concentration that we observed is consistent with results observed previously among both women with PCOS 22,23 and postmenopausal women.…”
Section: Commentsupporting
confidence: 91%
See 2 more Smart Citations
“…With regard to the bioavailability of testosterone, the largest study to date demonstrated a negative relationship between vitamin D and fT among postmenopausal women, 14 which is consistent with our findings. With regard to SHBG, the positive relationship with vitamin D concentration that we observed is consistent with results observed previously among both women with PCOS 22,23 and postmenopausal women.…”
Section: Commentsupporting
confidence: 91%
“…With regard to SHBG, the positive relationship with vitamin D concentration that we observed is consistent with results observed previously among both women with PCOS 22,23 and postmenopausal women. 14,24 However, our positive finding conflicts with results from the aforementioned meta-analysis; 21 our study’s larger cohort (and therefore greater power) may also explain why we found a relationship between vitamin D and SHBG while the meta-analysis did not.…”
Section: Commentcontrasting
confidence: 81%
See 1 more Smart Citation
“…We also newly showed that deficient 25(OH)D was more strongly associated with an adverse lipid profile of higher LDL-C and lower HDL-C in women compared to men. We previously have found that lower 25(OH)D was associated with a more androgenic sex hormone pattern in women,[25] which may be another potential mechanism how vitamin D impacts HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…This result might be attributed to the different levels of androgenic hormones among men and women. The testosterone level was higher among men than among women . A prior study showed that testosterone level is a predictor of handgrip strength among men .…”
Section: Discussionmentioning
confidence: 85%